ChatGPT as scaffold: quiz performance across session complexity - Fatima Ezzahra Kabba; Zouhair Ejbari (International Journal of Evaluation and Research in Education (IJERE), 2026)
Many studies examine the use of ChatGPT in education, but most measure student perceptions, not performance, and few track performance across multiple sessions of different complexity. In particular, no study has tracked whether this association varies across sessions of different cognitive complexity. Using a quasi-experimental design, first-year undergraduates (N=193) at the Higher International Institute of Tourism (ISITT) in Tangier, Morocco were followed across seven introductory statistics sessions. One group had access to ChatGPT during learning activities, while the other followed the same instruction without artificial intelligence (AI) access. Performance was measured through end-of-session quizzes (1,136 observations) and analyzed using a linear mixed-effects model. No consistent overall advantage was associated with either condition. However, a significant interaction between condition and session was identified (χ²(6)=61.50, p